Deepening Democracy and Enhancing Sustainable Livelihoods in Uganda: an Independent Review of the Performance of Special Interest Groups in Parliament - Bainomugisha, Arthur; Mushemeza, Elijah D. (ACODE Policy Research Series, 2006)
Uganda is currently going through a political transition process. To most political commentators, yet another milestone in the democratic development of a country whose 44 years of post-independence period have been marred by political anarchy and violence. After almost 20 years under a no-party political system, Uganda has reintroduced a multiparty political system. Most political analysts have observed that the way the political transition and constitutional reforms are handled will determine whether or not Uganda will have a peaceful democratic transition and consolidation of democracy. Critical in the constitutional reform and political transition processes is the institution of Parliament which is central to the amendment of the 1995 Constitution to provide for the necessary political reforms. The legislature in any democratic society is considered the most fundamental arm of the state in promoting democratic governance. Parliament in true democracies serves to secure the foundations of democracy by translating the will of the people into the law of land. At its core, the legislature is a mirror of society’s soul. The question is how to ensure that the composition of the legislature and the decisions it makes are a true reflection of the will of all people whom this body is designed to represent. The Parliament of Uganda, like in most post-conflict societies, is well placed to provide a mechanism for conflict prevention and management by creating conditions for sustainable development and stability. The composition of the sixth and seventh Parliament of Uganda was very diverse. Both parliaments were composed of directly elected members of Parliament and representatives of special interests groups such as women, persons with disability, workers, youths and the army elected under the principle of affirmative action to represent the voices of the marginalized.